2022
DOI: 10.1186/s12951-022-01479-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent development of contrast agents for magnetic resonance and multimodal imaging of glioblastoma

Abstract: Glioblastoma (GBM) as the most common primary malignant brain tumor exhibits a high incidence and degree of malignancy as well as poor prognosis. Due to the existence of formidable blood–brain barrier (BBB) and the aggressive growth and infiltrating nature of GBM, timely diagnosis and treatment of GBM is still very challenging. Among different imaging modalities, magnetic resonance imaging (MRI) with merits including high soft tissue resolution, non-invasiveness and non-limited penetration depth has become the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 188 publications
0
16
0
Order By: Relevance
“…However, multimodal imaging in combination with MRI with other modalities synergistically integrates these results, overcoming the difficulties of each technique, and offering enhanced morphological and pathophysiological information on GBM tumors. Further, in addition to current MRI probes, double- or triple-modal nanoprobes may be utilized in multimodal imaging to improve imaging of the brain GBM sites to enhance GBM therapy and increase the survival of patients [ 223 ].…”
Section: Future Treatment Perspectivesmentioning
confidence: 99%
“…However, multimodal imaging in combination with MRI with other modalities synergistically integrates these results, overcoming the difficulties of each technique, and offering enhanced morphological and pathophysiological information on GBM tumors. Further, in addition to current MRI probes, double- or triple-modal nanoprobes may be utilized in multimodal imaging to improve imaging of the brain GBM sites to enhance GBM therapy and increase the survival of patients [ 223 ].…”
Section: Future Treatment Perspectivesmentioning
confidence: 99%
“…29 A recent study revealed that EVs injected intranasally succeeded at delivering curcumin to the inflammatory site of the brain, offering an effective method for the treatment of brain inflammatory illnesses. 32 Taken together, EVs are emerging and efficient carriers to deliver drugs to the brain and hold great promise for translation to the clinic.…”
Section: Bing Guomentioning
confidence: 99%
“…Therefore, multifunctional nanocomposites in cores can be employed to target tumors using the cell membrane as a “tactical shell” to achieve multimodal imaging. Multimodal imaging, also called multiplexed imaging, is the process of producing signals for more than one imaging method simultaneously. , Multimodal imaging enables the simultaneous examination of multiple molecules, allowing cellular events to be examined simultaneously or their progression to be tracked in real time . In a recent work based on the above idea, bio-orthogonally labeled brain tumor cell membrane-coated nanocomposites were made to diagnose GBM.…”
Section: Nanomaterials Used In Brain Cancersmentioning
confidence: 99%